2010
DOI: 10.3390/toxins2082083
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Nephropathic Responses to Oral Administration of Extract of Cultured Penicillium polonicum in Rat and Primate

Abstract: Liquid- or solid substrate-cultured Penicillium polonicum administered in feed to rats over several days evokes a histopathological response in kidney involving apoptosis and abnormal mitosis in proximal tubules. The amphoteric toxin is yet only partly characterized, but can be isolated from cultured sporulating biomass in a fraction that is soluble in water and ethanol, and exchangeable on either anion- or cation-exchange resins. After several weeks of treatment renal proximal tubule distortion became strikin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…There is also the elusive silent nephropathic metabolite of the common food-borne mould Penicillium polonicum , causing rat renal apoptosis and one DNA adduct [ 35 ]. Chronic ingestion results in striking karyomegaly in the outer stripe of the outer medulla [ 36 ], a histopathological feature of topical interest also for OTA carcinogenicity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also the elusive silent nephropathic metabolite of the common food-borne mould Penicillium polonicum , causing rat renal apoptosis and one DNA adduct [ 35 ]. Chronic ingestion results in striking karyomegaly in the outer stripe of the outer medulla [ 36 ], a histopathological feature of topical interest also for OTA carcinogenicity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This focuses on proximal tubules in the outer stripe of the outer medulla (OSOM) in response to a Penicillium polonicum –moulded wheat extract, causing striking karyocytomegalic changes in the rat but no response in a vervet monkey (15). Karyomegaly is widespread within OTA renal tumours (1).…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate that rat responses do not automatically translate to the human, and concerning the renal karyomegaly found in OTA-treated rats, it is difficult to ignore contrasting findings in another mycotoxin-induced nephrotoxicity. This focuses on proximal tubules in the outer stripe of the outer medulla (OSOM) in response to a Penicillium polonicum –moulded wheat extract, causing striking karyocytomegalic changes in the rat but no response in a vervet monkey ( 15 ). Karyomegaly is widespread within OTA renal tumours ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fungus has also been isolated from meat products across several Mediterranean latitudes. P. polonicum was the most abundant mould contaminant in previous Balkan nephropathy studies [ 2 , 3 ]; although never found to produce OTA, it did commonly produce a novel nephrotoxin, expressed notably in the rat but not the primate [ 15 , 16 , 17 , 18 ]. It would be interesting if this species in China has similar toxigenic potential.…”
mentioning
confidence: 99%